Study and Prediction of Land Use/Cover Change in Small and Medium-Sized River Basins in Typical Urbanization Areas - LI Liujie; LIU Bingjun; WEI Qiuying (Renmin Zhujiang)
In order to explore the spatio-temporal evolution pattern of land use in small and medium-sized river basins under the background of rapid urbanization,this paper studied the Baiyun Lake basin and analyzed the structure change in land use in the Baiyun Lake basin from 1980 to 2020 by using land use dynamic degree and land use intensity.In addition,the paper employed a standard deviation ellipse model to analyze the spatial pattern change in the basin,discussed the influence on the land use in the basin before and after the completion of Baiyun Lake,and utilized a CA-Markov model to simulate the land use in the basin in the 2030 and explore the pattern evolution trend of land use in the basin in the future.The results show that:① The land in the Baiyun Lake basin from 1980 to 2020 was mostly used for construction,with an average annual proportion of 51.77%,and in 2020,the proportion reached 70.13%.② In the past 40 years,the land use in the basin has changed from cultivated land,dry land,forest,and grassland to construction land.The land use intensity has continued to rise,and the land structure has gradually tended to be single.③ Baiyun Lake occupies part of the urban land,so the land use in the basin will focus on the adjustment of forest and construction land in 2030.The land use intensity will change slowly,and the urban construction space will be controlled to a certain extent.